Massive Liver Replacement by Transplanted Hepatocytes in the Absence of Exogenous Growth Stimuli in Rats Treated with Retrorsine - Laconi, Sergio (American Society for Investigative Pathology, 2001)
A strategy for hepatocyte transplantation was recently developed whereby massive replacement of the recipient liver is achieved after a combined treatment with retrorsine, a pyrrolizidine alkaloid, and partial hepatectomy. We now investigated whether liver repopulation could occur in this animal model in the absence of any exogenous growth stimuli (eg, partial hepatectomy) for the transplanted cells. Dipeptidyl-peptidase type IV-deficient (DPPIV(−)) rats were used as recipients. Rats were given two injections of retrorsine (30 mg/kg each, 2 weeks apart), followed by transplantation of 2 × 10(6) hepatocytes isolated from a normal, syngeneic, DPPIV(+) donor. At 2 weeks after transplantation, clusters of DPPIV(+) hepatocytes occupied 3.3 ± 0.9% of host liver, increasing to 38.2 ± 6.3% at 2 months, and to 65.9 ± 8.8% at 5 months. By 1 year, >95% of the original hepatocytes were replaced by donor-derived cells. Serum parameters related both to hepatocyte function and integrity (including glucose, bilirubin, total proteins, cholinesterase, alanine aminotransferase, and alkaline phosphatase) were in the normal range in retrorsine-treated and repopulated animals. These results provide further insights toward developing strategies for effective liver repopulation by transplanted hepatocytes with reduced toxicity for the host and potential clinical applicability.